Ten-Coordinate Lanthanide [Ln(HL)(L)] Complexes (Ln = Dy, Ho, Er, Tb) with Pentadentate N3O2-Type Schiff-Base Ligands: Synthesis, Structure and Magnetism - Tamara A. Bazhenova; Ilya A. Yakushev; Konstantin A. Lyssenko; Olga V. Maximova; Vladimir S. Mironov; Yuriy V. Manakin; Alexey B. Kornev; Alexander N. Vasiliev; Eduard B. Yagubskii (Magnetochemistry, 2020)
A series of five neutral mononuclear lanthanide complexes [Ln(HL)(L)] (Ln = Dy3+, Ho3+ Er3+ and Tb3+) with rigid pentadentate N3O2-type Schiff base ligands, H2LH (1-Dy, 3-Ho, 4-Er and 6-Tb complexes) or H2LOCH3, (2-Dy complex) has been synthesized by reaction of two equivalents of 1,1′-(pyridine-2,6-diyl)bis(ethan-1-yl-1-ylidene))dibenzohydrazine (H2LH, [H2DAPBH]) or 1,1′-(pyridine-2,6-diyl)bis(ethan-1-yl-1-ylidene))di-4-methoxybenzohydrazine (H2LOCH3, [H2DAPMBH]) with common lanthanide salts. The terbium complex [Tb(LH)(NO3)(H2O)2](DME)2 (5-Tb) with one ligand H2LH was also obtained and characterized. Single crystal X-ray analysis shows that complexes 1–4 have the composition {[Ln3+(HL)−(L)2−] solv} and similar molecular structures. In all the compounds, the central Ln3+ ion is chelated by two interlocked pentadentate ligands resulting in the coordination number of ten. Each lanthanide ion is coordinated by six nitrogen atoms and four oxygen atoms of the two N3O2 chelating groups forming together a distorted bicapped square antiprismatic polyhedron N6O4 with two capping pyridyl N atoms in the apical positions. The ac magnetic measurements reveal field-induced single-molecule magnet (SMM) behavior of the two dysprosium complexes (with barriers of Ueff = 29 K at 800 Oe in 1-Dy and Ueff = 70 K at 300 Oe in 2-Dy) and erbium complex (Ueff = 87 K at 1500 Oe in 4-Er); complex 3-Ho with a non-Kramers Ho3+ ion is SMM-silent. Although 2-Dy differs from 1-Dy only by a distant methoxy-group in the phenyl ring of the ligand, their dynamic magnetic properties are markedly different. This feature can be due to the difference in long-range contributions (beyond the first coordination sphere) to the crystal-field (CF) potential of 4f electrons of Dy3+ ion that affects magnetic characteristics of the ground and excited CF states. Magnetic behavior and the electronic structure of Ln3+ ions of 1–4 complexes are analyzed in terms of CF calculations.